Pemanfaatan Kawasan Mangrove Lantebung Sebagai Laboratorium Alam Berbasis Field Work Pada Mata Pelajaran Geografi - Musyawarah, Rahma (PT. Pubsains Nur Cendekia, 2024)
Natural laboratories are ideal locations for fieldwork activities as they provide authentic learning resources, enabling students to study natural processes, ecosystem dynamics, and human-environment interactions directly. The aim of this study is to examine the potential of the Lantebung mangrove area as a natural laboratory for geography learning. This research is classified as qualitative descriptive research. The results of the study show: 1) The Lantebung mangrove area has potential as a study object for geography learning based on fieldwork, including biodiversity and local community activities related to resource management and utilization; 2) the stages of fieldwork-based learning include planning, preparation of materials and logistics, activity briefing, field observation, data collection, discussion and analysis, as well as presentation and reflection; and 3) challenges in implementing fieldwork-based learning include location, diverse initial understanding of students, ecosystem disturbances, time, budget and logistics, coordination with local communities, as well as safety and health.